2006
DOI: 10.1177/107110070602700706
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Loading of Achilles Tendon Repairs: A Comparison of Polyester and Polyblend Suture

Abstract: The use of polyblend suture in a four-stranded Krackow configuration provides stronger repairs with less gap formation, which may provide increased security during early functional rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
0
35
1
2
Order By: Relevance
“…High-repetition, high-force cyclic loading is thought to most accurately model current trends for postoperative rehabilitation protocols that stress early range of motion, early weightbearing, and early light-resistance stressing of the repair. 2 Our testing method revealed biomechanical differences that may not be apparent with only single-trial displacement-driven load-to-failure testing, reproducing a more physiologic load nearing what has been proposed for early weightbearing with a shoe lift in place. 1 Traditional displacement-driven single load-to-failure trials were also included as a subsequent step to allow for comparison of our results with many previous studies.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…High-repetition, high-force cyclic loading is thought to most accurately model current trends for postoperative rehabilitation protocols that stress early range of motion, early weightbearing, and early light-resistance stressing of the repair. 2 Our testing method revealed biomechanical differences that may not be apparent with only single-trial displacement-driven load-to-failure testing, reproducing a more physiologic load nearing what has been proposed for early weightbearing with a shoe lift in place. 1 Traditional displacement-driven single load-to-failure trials were also included as a subsequent step to allow for comparison of our results with many previous studies.…”
Section: Discussionmentioning
confidence: 54%
“…1 Traditional displacement-driven single load-to-failure trials were also included as a subsequent step to allow for comparison of our results with many previous studies. 2,3,14,25 …”
Section: Discussionmentioning
confidence: 99%
“…Force displacement values analyzed included peak force to failure (N), stress at peak (MPa), elongation at failure, and Young's modulus (GPa). Definition of failure was more than 5 mm gap formation at the repair site [21,22].…”
Section: Biomechanical Evaluationmentioning
confidence: 99%
“…6 Suture fixation techniques for graft fixation come with a wide variety of biomechanical characteristics including suture selection, number of loops, and number of sutures. 3,7 Biomechanical studies have shown that the locking Krackow and locking SpeedWhip (Arthrex, Naples, FL) stitches provide secure methods of fixation and have similar resistance to suture-graft elongation and load to failure. 8,9 In these previous biomechanical studies, however, the constructs showed greater than 10 mm of elongation under cyclic loading at 200 mm/min to 200 N for 200 cycles.…”
mentioning
confidence: 99%